OP19 Unlocking The Potential Of Established Products: Need For Incentives. (12th January 2018) - Nayroles, Gabrielle; Gabriel, Sylvie; Toumi, Mondher; Kornfeld, Åsa; Jaros, Patrycja; Frybourg, Sandrine; Antoñanzas, Fernando; Espín, Jaime; Martini, Nello; de Pouvourville, Gérard; Tolley, Keith; Wasem, Jürgen; et al.
Abstract : INTRODUCTION: Re-purposing of established products (EPs) – defined as marketed for 8 years or more – may represent a high value for patients and society. It has been recognized by the European Commission as an important factor contributing to greater access to new therapies. Due to a lower development cost, it could also represent a cost-effective alternative and help to reduce pressure on healthcare budgets. However, it is perceived that no financial incentives exist for the pharmaceutical industry to invest in new indications for EPs. The objective of this research was to review current European regulations and propose strategies stimulating development in this field. METHODS: We performed a targeted literature review and held two international expert panel workshops to discuss current policies and their implications, and issue recommendations for changes. RESULTS: Within the current regulatory framework EPs face price cuts due to generic competition, reference pricing (RP), price re-negotiations or systematic price cuts, after a period of marketing presence. Extension of indications does not permit to increase or maintain the price. Generic substitution regardless of indication poses another challenge. Limited incentives in the form of an additional year of market protection exists only for new indication(s) registered within the first 8 years following initial approval. The expert panel proposed several strategies to stimulate development in this field, including: (i) extending the period in which registering a new indication results in additional market protection beyond 8 years and extending the duration of additional market protection; (ii) delaying inclusion in RP for EPs with a new value adding indication; (iii) establishing a differential pricing by indication; (iv) preventing temporarily generic substitution when an EP is prescribed for a new indication. CONCLUSIONS: Current regulations represent a serious disincentive to develop new indications for EPs. Regulatory and pricing policy changes are needed to stimulate development in this important field.